A Protective effect of (Andrographis Paniculata) on 4-Vinylcyclohexene Diepoxide Induced ovarian Toxicity in Female Albino Rats: introduction - nuraddin, shahida; Bushra Ahmed Hamdi (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
Abstract Background and objective: Protective effect of (Andrographis Paniculata) on 4-Vinylcyclohexene Diepoxide. Material and methods:A group of 55 female albino rats undergo experiment on the outcome effect of 4-vinylcyclohexene Diepoxide injection for a priod of two weeks, as well as treatment effect of methanolic leaf extract of Andrographis paniculata oral administration for four weeks. Injection concentrations (160 and 320mg/kg. B.W) also two different doses of treatment (100 and 200mg/kg. B.W) have been applied. Results:The results on body weight and ovary weight were more evident when higher concentration dose was applied. Whereas, both induced dose were effective and no significant difference was recorded. Histological examination of ovary induced clearly the effect in various ovary tissues, and accumulation of connective tissue collagen fibers around corpus luteum where as a higher dose of treatment found to be behind sign of re-normalizing the within four weeks of treatment. Conclusion: More detailed study proposed to findout the exact right dose for treatment and may the further study extend to include other medicinal plant that might be more efficient. Keywords: 4-Vinylcyclohexene Diepoxide(VCD), Andrographis Paniculata Leaf, Ovarian Toxicity, Rats.